Síntese, estudo in silico, elucidação teórica da estereoquímica e atividade antifúngica de novas imidas derivadas do safrol análogas à podofilotoxina - Vilela, Raquel Finazzi (2020)
Among nitrogenous compounds, imides represent important building blocks for the development of new drugs, considering that this class of compounds contains a wide range of biological activity, such as: antimicrobial, antitumor, anticonvulsant, antispamodic, analgesic, fungicide, bactericide, herbicide and more. In this sense, the aim of this study was to synthesize cyclic imide derivatives, from safrole, amino acid and aromatic amines substituted as podophyllotoxin analogues, which are substances known in the literature due to their extensive biological activity as antitumor, antiviral, antidepressant, among others, and that can be used in the microbiological combat of resistant strains, tumor cells and that present themselves as alternatives to commercial drugs, drugs available in the pharmaceutical market. In this research, ten molecules were synthesized, nine of which are new and characterized by Spectroscopy IV, 1H NMR, 13C NMR and High Resolution Mass Spectroscopy. In order to obtain the compounds, the isomerization of Safrol (1) was necessary, using Potassium Hydroxide (KOH), to obtain the Isosafrol isomer (2). After this step, isosafrole was reacted with maleic anhydride, to obtain the product (3). This was purified by means of a chromatographic column. After purification, compound (3) was used as an intermediate, subsequently reacting with p-substituted aromatic amines and two amino acids (glycine and p-aminobenzoic acid) to obtain the final products (4a- j) with yields around 60%. In silico studies showed that the compounds met Lipinski's parameters, suggesting good oral bioavailability, good absorption, moderate solubility, and drug-likeness values indicated that the compounds are frequently present in most drugs currently used in the OSIRIS Property program Explorer, showing strong to moderate antifungal activity against various strains of Candida and Cryptococcus. In the biological assay in particular, compounds 4b, 4c and 4h exhibited strong antifungal activity, with MICs between 0.17 - 0.73 μmol mL-1 . The compound 4j exhibited antifungal activity with MIC 1.28 μmol mL- 1 for all strains tested. In silico studies for the Lipinski's five rule have indicated that these compounds have potential candidates for new drugs. Oral bioavailability was assessed using these parameters. In addition, a computational study helped to attribute the stereochemistry of compound 4j, where the synthesized mixture is composed of two stereoisomers, 4j (SRR) and 4j (RSS).